Penerapan Sistem Informasi Web untuk Optimalisasi Penjualan UMKM Kuliner Pujasera Walet Mas - Surahmat, Ahmad; Fua'dy, Tb Dedy; Korneilis; Adawiyah, Sugiarti Putri (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Currently, the food industry or culinary world is increasingly developing, marked by the proliferation of various fast food restaurants in big cities. Many consumers are not served well, they still use ballpoint pens and sales reports still use ledger books. This MSME sales data management information system uses the waterfall method with tools in the planning stage and UML (Unified Modeling Language) as a system modeling tool. As a goal of designing this system, it is designed to make it easier to record and manage data efficiently and to design applications to make ordering easier during the process. To overcome the problems above, a web-based information system for managing culinary food sales data using language was created. PHP and MySQL programming as a database. As a result of this research, there is a web-based culinary food sales data management information system. It is hoped that the management of culinary food sales data at the Pujasera Walet Mas Pujasera Walet Mas MSMEs in terms of sales and payment services can be served efficiently.